2003
DOI: 10.1034/j.1600-0609.2003.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

CD7 expression by CD34+ cells in CML patients, of prognostic significance?

Abstract: The purpose of the study was to identify a unique immunophenotype of normal or Philadelphia chromosome positive (Ph+) CD34+ cells that might be used to purify normal CD34+ cells from chronic myelogenous leukemia (CML) patients. An immunophenotypical study of CD34+ bone marrow cells of 20 patients with CML at diagnosis and during hydroxyurea treatment, and 39 controls were performed. All patients were Ph+, two patients had variant translocations and three patients displayed cytogenetic signs of clonal evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…It has shown that chromosomal anomalies in addition to the Ph chromosome are more commonly detected in the CD34+CD7+ Ph+ subset of CML cells than in the CD34+CD7- Ph+ subset, and patients with high levels of CD7 in CD34+ cells at diagnosis had a poor prognosis. Therefore, the level of CD7 in CD34+ cells at diagnosis has been considered an important prognostic marker for CML [14,15,16,19,20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has shown that chromosomal anomalies in addition to the Ph chromosome are more commonly detected in the CD34+CD7+ Ph+ subset of CML cells than in the CD34+CD7- Ph+ subset, and patients with high levels of CD7 in CD34+ cells at diagnosis had a poor prognosis. Therefore, the level of CD7 in CD34+ cells at diagnosis has been considered an important prognostic marker for CML [14,15,16,19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, HHT combined with Ara-C (HA regimen) should be potentially synergistic in eliminating both bulk leukemic cells and leukemic progenitors or stem cells in CML-MBC. In the present study, 34 patients with CML-MBC were treated with the HA regimen and its effect on bone marrow CD34+CD7+ cells, an important subpopulation of progenitor cells in CML-MBC [12,13,14,15,16], was analyzed among other clinical and homological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The Sokal score has also been successful in predicting survival in patients treated with hydroxyurea and, more recently, imatinib [5,6]. We and others have reported an increased expression of CD7 on CD34 + cells in some patients with CML [7][8][9], and high expression of CD7 confers an adverse prognosis which is independent of Sokal and Hasford scores [7,8]. In normal individuals, 4-5 % of CD34 + bone marrow cells express CD7 [10,11].…”
Section: Introductionmentioning
confidence: 97%
“…In normal individuals, 4-5 % of CD34 + bone marrow cells express CD7 [10,11]. Our previous study showed that, using a cut-off of 20 %, CML patients could be divided into two groups according to the level of expression of CD7 on their CD34 + bone marrow cells, and patients with w20 % CD34 + CD7 + cells had a significantly worse outcome than patients with v20 % CD34 + CD7 + cells [7]. Yong et al confirmed our results using molecular profiling of CD34 + cells procured by leukapheresis at diagnosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is also an independence prognostic factor and one of the important target for treatment [1][2][3] . It has been confirmed that about 1/3 CGL patients in chronic phase can get cytogenetic response with the treatment of homoharringtonine (HHT) alone [4][5][6][7] , but the mechanism needs further research.…”
mentioning
confidence: 99%